Dentoskeletal and facial features comparison between individuals treated with four first premolar extraction in the 1970s and in the new millennium - Araque, Rodrigo Andres Naveda (2019)
Introduction: The frequency of first premolar extractions in Orthodontics has remarkably decreased in the last 40 years. Objective: The aim of this study was to compare the dentoskeletal initial features of patients treated with four first premolar extractions in the 1970s and in the new millennium. Materials and Methods: Group 1 was composed by 30 subjects with Class I malocclusion (mean age of 12.8 years, 10 males, 20 females) treated in the 1970s with four first premolar extraction and comprehensive orthodontic treatment. Group 2 comprised 30 subjects with Class I malocclusion (mean age of 13.4 years, 13 males, 17 females) treated in the new millennium similarly to Group 1. Initial dental models and lateral cephalograms were digitized and measured using OrthoAnalyzerTM 3D software and Dolphin Imaging 11.0 software, respectively. Initial dentoskeletal features were analyzed and compared. Intergroup comparison was performed using independent t tests (p<0.05). Results: Group 2 showed an increased maxillary and mandibular protrusion, a greater maxillary and mandibular body lengths and an increased incisor protrusion in comparison to Group 1. Group 2 also showed a greater lower anterior facial height and a greater vertical development of molars and maxillary incisors. Conclusion: Patients with Class I malocclusion treated with four first premolar extraction in the new millennium present an increased degree of maxillomandibular, dental and labial protrusion, an increased lower anterior facial height, an acute nasolabial angle and similar anterior dental crowding compared to patients treated similarly in the 1970s decade. Severe bimaxillary skeletal and dental protrusion determined first premolars extractions in the new millennium.